THU0454 Questionnaire survey for gout-related knowledge level in 185 chinese physicians. (23rd January 2014) - Li, Q.H.; Li, Z.X.; Liu, H.J.; Lu, M.; Li, Y.H.; Ou-Yang, X.; Li, T.; Zou, C.J.; Schumacher, H.R.; Dai, L.
Abstract : Background: Our previous survey found that gout patients in south China have poor knowledge on urate-lowering therapy (ULT). Physicians are the main provider of disease knowledge for patients but few reports on physician knowledge about gout have been published. Objectives: To investigate gout knowledge level of physicians in South China. Methods: A multi-center survey in Guang Dong Province of 185 physicians from groups considered most likely to be consulted by gout patients conducted with a questionnaire adopted from Zhang et al [1] . Such physicians included residents and fellows who in this system often see patients with little supervision. The questionnaire was composed of 10 questions concerning essential areas of knowledge of gout. Physicians were considered as well aware of gout when they correctly answered 8 or more questions. Results: (1) 184 participants completed ≥8 questions. Among them, 17.9% were rheumatologists, 82.1% were non-rheumatologists including internal medicine physicians (38.6%), orthopedists (23.4%), traditional Chinese medical physicians (4.3%) and other specialists (15.8%). 86.7% were interested in gout. The mean number of correct answers of all participants was 8.3±1.4, with median value 9 (7-9). The mean of correct answers from rheumatologists was significantly higher than that of the non-rheumatologist group (9.6±0.53 vs 8. 0±1.4, P<0.05). (2) Both groups were well informed (correct answer rate of all participants >85%) about the cause of gout, crystals causing attacks, the characteristics of acute attacks, the most effective drugs for acute attacks and common complications of gout. For the ULT related knowledge, only 75.0% of non-rheumatologists knew that allopurinol is a kind of urate-lowering drugs, 55.3% knew optimal SUA target level and 42.8% knew that urate-lowering drugs should be taken life-long. 84.8% of rheumatologists and 74.8% of non-rheumatologists knew how to prevent attacks induced by ULT. The calculated adequate awareness rate of all participants was 73.4% and the awareness rate of the rheumatologist group was significantly higher that that of the non-rheumatologist group (100.0% vs 67.5%, P<0.05). The awareness rate of participants who were interested in gout was significantly higher than those not (76.9% VS 45.8%, P<0.05). Logistic regression showed that the number of consulted gout patients per year significantly predicated the non-rheumatologists' awareness of gout-related knowledge. Conclusions: Chinese rheumatologists and trainees were generally very familiar with gout related knowledge. However, the non-rheumatologist had relatively poor knowledge on ULT. The further CME for Chinese non-rheumatologist should emphasize the use of urate-lowering drugs, treatment duration, optimal target SUA level and prevention of attacks on initiating ULT. References: Zhang LY, et al. Development and evaluation of a survey of gout patients concerning their knowledge about gout.J Clin Rheumatol, 2011;17:242-248 Disclosure of Interest: None Declared